Reviewing The Role of Destination Brand Identity in Sustainable Tourism Destinations - Chrisna Riane Opod; Tjokorda Gde Raka Sukawati; I Putu Gde Sukaatmadja; Gede Suparna (Journal of International Conference Proceedings, 2025)
Sustainable tourism has become a central theme in destination development worldwide, driven by increasing awareness of tourism’s environmental, social, and cultural impacts. Within this context, Destination Brand Identity (DBI) plays a crucial role in shaping tourist perceptions and enhancing the long-term competitiveness of destinations. This study presents a systematic literature review using a qualitative approach aimed at examining the contribution of DBI to sustainable tourism destinations. A total of 20 peer-reviewed articles published over the past decade were critically analyzed, focusing on five core themes: (1) DBI dimensions that support sustainability; (2) the role of DBI in enhancing destination sustainability; (3) the integration of DBI with sustainable branding practices; (4) community engagement and local representation in DBI formation; and (5) methodological developments in DBI and sustainable tourism studies. The findings are expected to enrich the academic discourse on DBI and provide practical insights for sustainable destination management.